Implementasi Asas No Work No Pay Dalam Pemenuhan Hak Pekerja/Buruh Perempuan Berdasarkan Pasal 82 Ayat (2) Undang-Undang Nomor 13 Tahun 2003 - Mustika Prabaningrum Kusumawati (Universitas Medan Area, 2022)
Female workers/laborers are in a vulnerable condition compared to male workers/laborers. Naturally, female workers/laborers experience pregnancy and even in the worst condition, miscarriage. No woman wants this miscarriage condition and if this condition is experienced by female workers/laborers it will have an impact on the performance and production process of the company. This is because it is certain that female workers/laborers cannot work because of these conditions. This study aims to find out the essence of implementing the no work no pay principle in fulfilling the rights of female workers/laborers who experience miscarriages based on Article 82 paragraph (2) of Law Number 13 of 2003 concerning Manpower. This research is a normative legal research with a descriptive analytical nature using a literary approach and a field approach. The analysis of the data obtained in this study was carried out qualitatively. The results of the research show that the no work no pay principle does not apply absolutely. This is because there are several exceptions in Law Number 13 of 2003 concerning Manpower which requires employers to continue to pay their workers/laborers wages even if they are not working when workers/laborers use their right to rest, one of which is for female workers/laborers who experience miscarriages